2021
DOI: 10.1038/s41598-021-98397-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of visually assessed right ventricular dysfunction in patients with septic shock

Abstract: We retrospectively analyzed data from the Medical Information Mart for Intensive Care-III critical care database to determine whether visually-assessed right ventricular (RV) dysfunction was associated with clinical outcomes in septic shock patients. Associations between visually-assessed RV dysfunction by echocardiography and in-hospital mortality, lethal arrhythmia, and hemodynamic indicators to determine the prognostic value of RV dysfunction in patients with septic shock were analyzed. Propensity score ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…[16,39] In the early phase of sepsis, left ventricular ejection fraction (LVEF) is not impaired; however, stroke volume is low because of insufficient cardiac preload resulting from high vascular permeability and vasodilation. [16,39,40] The heart rate may increase to compensate, although it is often insufficient to maintain adequate cardiac output. [16,39] In severe sepsis, after increased fluid loading and permeability, stroke volume can recover, particularly in survivors, while LVEF temporarily decreases, partly because of www.md-journal.com a higher LV end-diastolic volume.…”
Section: Mechanistic Changes To the Heart Underlying Septic Cardiomyo...mentioning
confidence: 99%
See 4 more Smart Citations
“…[16,39] In the early phase of sepsis, left ventricular ejection fraction (LVEF) is not impaired; however, stroke volume is low because of insufficient cardiac preload resulting from high vascular permeability and vasodilation. [16,39,40] The heart rate may increase to compensate, although it is often insufficient to maintain adequate cardiac output. [16,39] In severe sepsis, after increased fluid loading and permeability, stroke volume can recover, particularly in survivors, while LVEF temporarily decreases, partly because of www.md-journal.com a higher LV end-diastolic volume.…”
Section: Mechanistic Changes To the Heart Underlying Septic Cardiomyo...mentioning
confidence: 99%
“…[13] A recent study demonstrated that visual assessment of RV function using echocardiography in patients with septic shock revealed that RV dysfunction was associated with lower cardiac output, pulmonary artery pressure index, and RV stroke work index. [40] Figure 1. Pathophysiology and mechanisms of septic myocardial dysfunction.…”
Section: Changes To the Heart In Sepsismentioning
confidence: 99%
See 3 more Smart Citations